Metathesis catalysts : an integrated computational, mechanistic and synthetic study - Sabbagh, Ingrid Theresa (Rhodes University, Faculty of Science, Department of Chemistry, 2006)
An integrated approach to the design of potential rutheniun-based metathesis catalysts is described, in which closely defined synthetic forays provide the focus and rationale for detailed computational and mechanistic studies. The ground-state geometry of a 1st-generation Grubbs catalyst has been explored at the molecular mechanics, semi-empirical and DFT levels, and the resulting structures have been shown to compare favourably with literature data and with the structure of a known crystalline analogue. The DMolÂ³ DFT code has also been shown to represent accurately both the geometry of the corresponding co-ordinatively unsaturated monophosphine derivative, and the ligand dissociation energy associated with its formation. A DFT free-energy profile of the degenerate metathesis of ethylene has been generated, using a truncated model of the 1st-generation Grubbs catalyst, permitting location, for the first time, of the three expected transition states and providing new information regarding the rate-determining step. DFT methods have been used to facilitate the design of a tridentate camphor-derived ligand for use in the construction of a novel Grubbs-type catalyst. The phosphine ligand dissociation energy of the putative catalyst and the ethylene metathesis energy profile of a truncated model have also been studies at the DFT level. The attempted synthesis of the proposed ligand proceeded via a novel 8-bromocamphoric anhydride intermediate and afforded several unexpected and novel products, including a cisfused Î³-Iactone, and a bromo camphoric acid derivative. Single crystal X-ray analysis of the latter reveals a chiral, polymeric H-bonded packing arrangement, rendering it suitable for chiral inclusion studies. Computational methods, including the GAUSSIAN-based GIAO NMR prediction technique, were used to support the structural characterisation of the novel camphor derivatives. DFT-Ievel computational analysis of the C-8- and C-9 bromination of camphor has afforded theoretical insights which permit the reconciliation of two earlier empirical explanations regarding the regioselectivity of these transformations; moreover, the theoretical results suggest that a third, previously disregarded factor, plays a significant role. A coset analysis, in conjunction with DFT-Ievel energy profiling, has also been used to resolve conflicting opinions regarding the origin of the major byproduct. Computed electronic parameters (CEP's) have been calculated for the anionic ligands involved in a series of 2nd-generation Grubbs-Hoveyda-type catalysts, and used to explain some apparently anomalous trends in catalyst activity. A linear relationship between ligand CEP's and selected Â¹H NMR chemical shifts has also been demonstrated and used to identify a transient ruthenium complex in solution. The ability of the malonate di-anion to bind to ruthenium in a bidentate manner has been explored and demonstrated, under suitable conditions. DFT methods have been used to design and assess the ruthenium-chelating potential of a novel tridentate malonate derivative. A synthetic pathway to this ligand has been designed and several novel heterocyclic intermediates have been isolated and characterised. An NMR-based kinetic study of the Grubbs-catalysed self-metathesis of l-octene has been completed, and the effects of temperature, concentration and solvent variations on the kinetic parameters have been studied. Application of the Guggenheim method and a simplified mechanistic model has permitted the accurate calculation of pseudorate constants for the initiation and, for the first time, the propagation phase of the reaction. Theoretical studies of this reaction at the DFT and molecular mechanics levels have been shown to support previous assumptions regarding the selectivity and temperature-dependence of metallacycle formation.
Keywords: Metathesis (Chemistry); Catalysis; Metal catalysts; Chemical kinetics